2015
DOI: 10.1128/cvi.00042-15
|View full text |Cite
|
Sign up to set email alerts
|

Human Invasive Muscular Sarcocystosis Induces Th2 Cytokine Polarization and Biphasic Cytokine Changes, Based on an Investigation among Travelers Returning from Tioman Island, Malaysia

Abstract: Sarcocystis nesbitti is a parasite responsible for a biphasic eosinophilic febrile myositis syndrome in two recent outbreaks in Malaysia. We demonstrate Th2 cytokine polarization in infected travelers, an overall cytokine production decrease in the early phase of the disease suggestive of initial immunosuppression, and elevated levels of proinflammatory and chemotactic cytokines in the later myositic phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…However, SWFCA did not suppress DC activation, but induced a mature pro-inflammatory DC phenotype that preferentially elicited Th1/Th17 responses, immune responses associated with S. fusiformis clearance (Gazzinelli et al 1993;Hayashi et al 1996;Manicassamy and Pulendran 2011). There is some supporting evidence which may explain the dichotomy observed between our findings and the reports from El Shanawany et al in which a study reported biphasic immune responses in infected humans, with a Th1 biased response being observed during the initial phase of infection, while during the muscle stage a Th2 response was observed which correlate with hyper-eosinophilia in invasive muscle tissue (Tappe et al 2015).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, SWFCA did not suppress DC activation, but induced a mature pro-inflammatory DC phenotype that preferentially elicited Th1/Th17 responses, immune responses associated with S. fusiformis clearance (Gazzinelli et al 1993;Hayashi et al 1996;Manicassamy and Pulendran 2011). There is some supporting evidence which may explain the dichotomy observed between our findings and the reports from El Shanawany et al in which a study reported biphasic immune responses in infected humans, with a Th1 biased response being observed during the initial phase of infection, while during the muscle stage a Th2 response was observed which correlate with hyper-eosinophilia in invasive muscle tissue (Tappe et al 2015).…”
Section: Discussionsupporting
confidence: 70%
“…However, studies have demonstrated that S. calchasi infection is associated with Th1 immune response at the schizogonic phase, which may facilitate evasion and suppression of host inflammatory response (Olias et al 2013). Humans infection with S. nesbitti in the initial phase of infection express low levels of IL-12, IFNc, RANTES, MCP-1 and IL12p70 while higher cytokines levels were detected in Phase II of infection (Tappe et al 2015). Phase I may point towards a decrease in T cell function and DC activation and recruitment as seen in other studies (Sallusto et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Nickdel et al [40] discussed that T. gondii infection cause's eosinophilia and increased the level of IL-5, with pathological changes in the small intestine, with a simultaneous reduction in IL-12 and IFN-γ. Moreover, a biphasic immune responses were characteristic in eosinophilic muscle invasive Sarcocystis infections with a Th1 response during the initial phase while in muscle stage, the Th2 response was abundant [41].…”
Section: Discussionmentioning
confidence: 99%